The Impact of Binahong Leaf Decoction on Perineal Wounds Healing Among Postpartum Women at Sikamali Clinic - Rutiana Rutiana; Nila Widya Keswara; Rani Safitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Perineal wound healing in postpartum women is a crucial element of their rehabilitation.  If left untreated, these wounds can cause pain and consequences.  Natural substances, such as binahong (Anredera cordifolia) leaves, have been shown to have anti-inflammatory and antibacterial effects, which may speed up wound healing.  This study used a quasi-experimental design with two groups: the treatment group consumesd binahong leaf decoction water onece a day, and the control group didn’t get any treatment.  The study sample consisted of 30 postpartum women who had perineal lesions, selected using a purposive sampling technique.  To examine the progress of perineal wound healing, data were collected using questionnaires and observation sheets.  Descriptive and Fisher's test statistics used to determine the results. The results showed that 67.7% of mothers who consumed binahong leaf decoction water experienced faster wound healing compared to 33.3% of mothers in the control group. Bivariate analysis showed a significant effect between consumption of binahong leaf decoction water on accelerating perineal wound healing with a p value = 0.000 (p < 0.05). The flavonoids and saponins in binahong leaves play a role in the process of tissue regeneration and collagen synthesis, which supports the acceleration of wound healing. Demographic factors such as age, education, and employment status also contribute to the effectiveness of wound care. Binahong leaf decoction is effective in accelerating perineal wound healing in postpartum women. The use of this natural ingredient can be a safe and accessible alternative treatment, so it can be recommended in midwifery practice to improve the quality of postpartum care.